Culturally safe, high‐quality breast cancer screening for transgender people: A scoping review protocol. (24th November 2021) - Peters, Micah D. J.; Ramsey, Imogen; Kennedy, Kate; Sharplin, Greg; Eckert, Marion
Abstract: Aim: To develop evidence‐based recommendations for provision of culturally safe, high‐quality services for breast cancer screening for transgender people. Design: The scoping review will follow the JBI methodological guidance for scoping reviews. Methods: A search using MEDLINE (PubMed), Embase (Ovid), Scopus, the Cochrane Library, including the Cochrane Methodology Register, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and the World Health Organization, Australia Government Department of Health and Google Scholar will be undertaken. The review will include people of any age and ethnicity defined in the source of evidence as transgender. The review will include individuals who have used gender‐affirming interventions or not and sources of evidence that report information relevant to the provision of culturally safe, high‐quality breast cancer screening services for transgender people. English language sources of evidence published from database inception with information from any country will be eligible for inclusion. Sources will be screened for inclusion by three independent reviewers. Results will be extracted using a purpose‐built tool and presented in relation to the review questions and objective in the final report using tables, figures and corresponding narrative. Project funding was approved by the Australian Government Department of Health in June 2020. Discussion: There are a range of factors that impact on the equity of health access and outcomes for people who are not cisgender. Transgender people are at risk of breast cancer but there is relatively little evidence about how their risks may or may not differ substantially from cis‐gendered individuals and little guidance for health providers to ensure inclusive, culturally safe, high‐quality breast cancer screening services for both transgender males, transgender females and gender diverse people who may not identify as male or as female. Impact: It is important to provide culturally safe, high‐quality services for breast cancer screening for transgender people.